Transforming family dynamics: unexpected positive effects of treatment for adolescent gaming problems on family relationships - Kapetanovic, Sabina; Due Nielsen, Maiken; Gurdal, Sevtap; Claesdotter-Knutsson, Emma (Frontiers in Developmental Psychology, 2024)
IntroductionWhile parenting is important for the development of adolescent problem gaming, it is unknown whether treatment of such problems in adolescents has a bearing on parenting. This study aims to explore the effects of individual relapse prevention (RP) treatment for adolescent problematic gaming on parenting practices and family dynamics.MethodsA total of 72 adolescents (74% male; Mage = 14.5 SD = 1.4), participated in the study, with n = 39 in the intervention group and n = 33 in the control group. Pre- and post-treatment data were collected on parenting practices (e.g., monitoring and communication) and family dynamics. Changes in parenting measures were analyzed using the Wilcoxon signed-rank test and Svensson's method of change analysis.ResultsAdolescents in the intervention group reported reduced family conflict and changes in specific parenting practices, including less inquiry, fewer rules and intrusion regarding gaming post-treatment. In contrast, the control group reported a decline in family cohesion at post-treatment assessment.DiscussionThe results highlight adolescents' active role in shaping family dynamics and underscore the positive spillover effects of treating adolescent problematic gaming on parenting practices and family relationships. These findings are relevant to clinical practice and deepen our understanding of the relationship between adolescent gaming, parent-child interactions, and treatment spillover effects.Trial registration numberClinicalTrials.gov, NCT05506384, https://clinicaltrials.gov/ct2/show/NCT05506384.